2019
DOI: 10.1017/s135246581900050x
|View full text |Cite
|
Sign up to set email alerts
|

What do you really need? Self- and partner-reported intervention preferences within cognitive behavioural therapy for reassurance seeking behaviour

Abstract: Background:Reassurance seeking (RS) in obsessive compulsive disorder (OCD) is commonly addressed in cognitive behavioural therapy (CBT) using a technique called reducing accommodation. Reducing accommodation is a behaviourally based CBT intervention that may be effective; however, there is a lack of controlled research on its use and acceptability to clients/patients, and case studies suggest that it can be associated with negative emotional/behavioural consequences. Providing support to encourage coping with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Providing reassurance was the most highly endorsed accommodation behaviour, which is consistent with research showing it is highly sought by people with GAD (Rector et al, 2019;Woody and Rachman, 1994). It is likely that individuals with GAD seek reassurance from their partners with the aim of bolstering their feelings of safety and certainty regarding a particular outcome (Gústavsson et al, 2021;Halldorsson and Salkovskis, 2017;Neal and Radomsky, 2020). When reassurance is received, it temporarily alleviates distress by diminishing the perceived threat.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Providing reassurance was the most highly endorsed accommodation behaviour, which is consistent with research showing it is highly sought by people with GAD (Rector et al, 2019;Woody and Rachman, 1994). It is likely that individuals with GAD seek reassurance from their partners with the aim of bolstering their feelings of safety and certainty regarding a particular outcome (Gústavsson et al, 2021;Halldorsson and Salkovskis, 2017;Neal and Radomsky, 2020). When reassurance is received, it temporarily alleviates distress by diminishing the perceived threat.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, given the preliminary evidence that partner SA is associated with greater relationship satisfaction, a potential barrier to decreasing SA during treatment is increased relationship distress. As an alternative to eliminating SA behaviours, treatment could focus on changing the function of these behaviours from safety-seeking to supportive (Neal and Radomsky, 2019;Neal and Radomsky, 2020). In other words, instead of providing reassurance that a bad outcome will not transpire, the partner could provide encouragement to sit with the discomfort and engage in skills use (Neal and Radomsky, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests when people with OCD receive supportive feedback from their partner following an exposure task this can increase perceived helpfulness of the feedback given and reduce reassurance seeking behaviours compared with those whose partners were instructed to provide neutral or more generally supportive responses to reassurance seeking (Neal and Radomsky, 2019). Literature also suggests that people find this approach to treatment more acceptable than traditional CBT, which focused more on reducing accommodation to requests for reassurance (Neal and Radomsky, 2020). Dependent upon the individual's culture and beliefs, it may also be important to involve other individuals from the person's community, e.g.…”
Section: What Can Family Members Do Instead?mentioning
confidence: 99%
“…The main conclusions from that study were that a cognitive behavioural therapy which focuses on helping people who engage in ERS to shift from seeking reassurance to seeking support might be beneficial (Halldorsson and Salkovskis, 2017b). Further support for this intervention comes from recent work by Neal and Radomsky (2019, 2020), which has shown that support provision is both effective (Neal and Radomsky, 2019) and acceptable for patients and their caregivers (Neal and Radomsky, 2020).…”
Section: Introductionmentioning
confidence: 99%